Output feedback sliding mode control based on non-singular terminal sliding mode observer. (May 2023) - Chen, Yunjun; Jiang, Chao; Dong, Jiuzhi; Zhao, Zhanshan
In this article, the finite-time output feedback sliding mode control problem is investigated for a class of continuous-time linear systems with unmeasurable states. First, a novel terminal sliding mode observer is established to estimate the unmeasured system states. Second, a novel integral sliding surface is introduced with tunable parameters. Then, an output feedback sliding mode controller with power terms is constructed to drive the given system to the origin in a finite time. A switching from the terminal sliding mode to a usual sliding manifold is taken to avoid singularity problem. Finally, two application-oriented examples are offered to verify the effectiveness of the proposed algorithm.